Inbreeding status and implications for Amur tigers. (20th December 2021) - Ning, Y.; Roberts, N. J.; Qi, J.; Peng, Z.; Long, Z.; Zhou, S.; Gu, J.; Hou, Z.; Yang, E.; Ren, Y.; Lang, J.; Liang, Z.; et al.
Abstract: Inbreeding more likely occurs in small, isolated and endangered populations, and may influence the sustainable survival of a population. As the Amur tiger Panthera tigris altaica population in China experienced a severe decline in the 1990s, the recovering population may be prone to inbreeding and its potential impacts on population health. However, the inbreeding status has not been evaluated and relationships with health remain poorly understood in wild animals. Based on the genetic samples collected from the main Amur tiger habitats in China, this study analyzed the population inbreeding level, major histocompatibility complex polymorphism, parasitic infections and gut microbial structures and functions, and then explored the influence of inbreeding on these traits. Our results indicated that more than 50% of individual relationships were in cousin or half sibs, and 22.73% of individuals had moderate or high inbreeding coefficients. There was a significant positive correlation between the inbreeding level of an individual and the Toxocara cati parasitic load. Gut microbiota community structure and function were also impacted by inbreeding intensity. In conclusion, results indicate that the Amur tiger population in China has reached a moderate level of inbreeding and that there are direct interactions between inbreeding intensity and parasitic load and gut microbiota. This study thus provides an early warning on the Amur tiger population health and should prompt the construction of national and international ecological corridors and/or the re‐introduction of new individuals to relieve the evident inbreeding pressure. Abstract : Inbreeding stress of small population for Amur tigers has been checked and revealed the potential relationships with both parasite loads and intestine microbiota. These evidences showed that inbreeding may lead to the negative effects on population health. Genetic savings should be taken as conservation actions, i.e., through establishing corridors to connect other habitat patches or reintroduction of tiger cubs for mitigating the pressure of the inbreeding.